Monofunctional amines substituted fluorenylidene bridged cyclotriphosphazenes: 'Turn-off' fluorescence chemosensors for Cu2+ and Fe3+ ions. (24th November 2015) - Şenkuytu, Elif; Tanrıverdi Eçik, Esra; Durmuş, Mahmut; Yenilmez Çiftçi, Gönül
Graphical abstract: The synthesis and characterization of the first series of amine substituted fluorenylidene-bridged cyclotriphosphazene derivatives were reported in this study. The florescence properties and chemosensor behaviors of the synthesized new compounds against to metal ions were studied. The fluorenylidene bridged 2-naphthylamino substituted cyclotriphosphazenes showed fluorescence chemosensor behavior with high selectivity for Fe 3+ and Cu 2+ ions in the solution. Abstract: In the present work, the reaction of 2, 2, 4, 4-tetra(anilino)-6, 6-dichlorocyclotriphosphazene (4 ) and 2, 2, 4, 4-tetra(2-naphthylamino)-6, 6-dichlorocyclotriphosphazene (5 ) with 4, 4′-(9-fluorenylidene)diphenol, FDP, (6 ) and 4, 4′-(9-fluorenylidene)dianiline FDA (7 ) were studied in THF and new aniline (8 and9 ) and 2-naphthylamine (10 and11 ) substituted FDP-bridged cyclotriphosphazenes and aniline (12 ) and 2-naphthylamine (13 ) substituted FDA-bridged cyclotriphosphazene derivatives were obtained. All newly synthesized monofunctional amines substituted fluorenylidene bridged cyclotriphosphazenes (8 –13 ) were fully characterized by elemental analysis, 1 H and 31 P NMR spectroscopies, MALDI-TOF mass spectrometry and UV–Vis electronic absorption spectra. The florescence properties of the synthesized new compounds were studied. The chemosensory behavior of the compounds against to metal ions was also investigated. The obtained fluorenylidene bridged 2-naphthylamine substituted cyclotriphosphazenes (10, 11 and13 ) showed fluorescence chemosensor behavior with high selectivity for Fe 3+ and Cu 2+ ions in the solution.